Frame Structure and Engineering Applications of the Multisource System Cloud Service Platform of Monitoring of the Soft Rock Tunnel. (15th February 2021) - Wang, Fengnian; Yin, Songyang; Guo, Aipeng; Wang, Zhicai; Mi, Meng; Qi, Gan; Ma, Juan; Zhang, Haijiang
Abstract : Throughout engineering construction, large deformation disasters in soft rock tunnels are encountered increasingly frequently. Therefore, structural health monitoring not only ensures accurate construction management but also provides a basis for dynamic adjustment of the support structure. The existing monitoring technology has certain shortcomings, such as poor anti-interference ability, non-real-time operation, and great security risks. Consequently, high-precision real-time monitoring has become a key scientific issue in tunnel engineering. For this work, multisource information fusion technology was adopted, while data security reserve systems, such as cloud server (ECS) based on the fiber Bragg grating multisource sensing system, cloud database (RDS), and cloud website, were embedded into the No. 2 inclined shaft of the Muzhailing tunnel. Based on the negative Poisson's ratio (NPR) anchor cable control technology for large deformation of the soft rock in the No. 2 inclined shaft of the Muzhailing tunnel, reasonable and effective intelligent monitoring was carried out for tunnel construction. Monitoring and early warning cloud service platforms, based on the Internet of Things and cloud technology, could quickly produce query and statistic tunnel monitoring information. The monitoring system provided the collection, transmission, storage, processing, and early warning information sending of data, such as NPR anchor cable axial force, steel arch stress, deep surrounding rock displacement, surrounding rock deformation, and contact pressure between primary support with secondary lining. This monitoring system ensured construction safety and provided monitoring application case support for the related problems of similar projects.